DETERMINANTS OF LEARNERS’ PERCEIVED LEARNING ON ENGLISH VOCABULARY LEARNING APPLICATION - Shi, Fengyi; Phongsatha, Satha (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Purpose: In the digital information age, English vocabulary learning application, as a mobile learning method, has been widely welcomed by learners. But most products of the same type are very similar in the market. Therefore, how to find the factors that affect learners’ perceived learning, and based on these factors, provide learners with more diversified services that match their needs, break the status quo of product homogeneity, is a problem worth thinking and studying at present. Research Design Data and Methodology: This study takes learners as the core, constructivism theory as the basis and questionnaire survey as a research instrument to study learners’ perceived learning on English vocabulary learning application. Through an extensive review of previous relevant literature, four factors of motivation, dialogue, course design and layout design that may influence perceived learning were selected. 150 University students matching the population requirements were picked as sample on an online questionnaire platform, 150 questionnaires were returned, and all valid data were used to test hypotheses. Results: The results show that motivation, dialogue, course design and layout design all have significant influence on perceived learning. Conclusion: All of the four factors influenced the students’ perceived learning. The motivation was shown to have the most influence and the teachers and application developer should consider how the students’ motivation can be improved to enhance their experience of the learning and application. Keywords: Perceived learning, Student’s Motivation, Students’ dialogue, Course Design JEL Classification Code: A22, I23, L86